IMPLEMENTASI INTEGRATED MARKETING COMMUNICATION MELALUI BRAND ACTIVATION DALAM MENINGKATKAN BRAND AWARENESS KAI WISATA - Ramadhani Regita Zein, Nadia; Mutiah, Tuty; Saputra Dewa, Faris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
KAI Wisata continues to strengthen its corporate brand by implementing various brand activation programs designed to increase public awareness of its tourism services. This study examines how communication strategies are applied within these activities and evaluates their contribution to enhancing brand awareness. A descriptive qualitative approach was employed through in depth interviews, direct observation, and documentation. Data were analyzed using the concepts of Integrated Marketing Communication (IMC), communication strategy, brand activation, and brand awareness. The findings indicate that the company integrates multiple communication elements, including advertising, sales promotion, public relations, personal selling, direct marketing, and event and experience, to create meaningful interactions with its target audience. These activities are reinforced by the selection of competent communicators, audience oriented message development, the use of diverse communication media, and the implementation of interactive engagement during brand activation events. As a result, the communication strategy contributes to strengthening brand recognition and brand recall among participants. Nevertheless, continuous communication efforts are still required to achieve stronger top of mind awareness and broaden public understanding of the company's comprehensive range of tourism services.